Reorientasi Minat Anak terhadap Fiksi: Studi Perbandingan Nilai Sosial Emosional dalam Cerita Rakyat Indonesia dan Cerita Anomali Digital - Citra Lestari; Agus Nuryatin; Mukh Doyin; Yusro Edy Nugroho (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
Children’s interests shift from traditional fiction to digital storytelling, indicating a preference for emotionally intricate and character-focused narratives. A poll of 113 Indonesian children aged 8 to 12 provided additional insights into their preferred types of stories. This study examines the implications of this transformation for educational objectives, particularly about cultivating social and emotional competencies and fostering character development. Six narrative texts were analyzed utilizing a qualitative methodology. Three Indonesian folktales were selected due to their narrative composition and factual foundation. The last three were anomaly-themed digital narratives from popular TikTok accounts frequented by children, including @cerita_anomali_lucu, @pylan.page, and @piq.man6, each boasting millions of views and likes. We utilized NVivo 15 software to assist us with thematic coding. We examined three domains of character education (empathy, integrity, and accountability) and two facets of social-emotional learning (SEL) (emotion management and relational skills). The findings indicate that Indonesian folktales consistently provide explicit moral teachings and enhance emotional intelligence. Conversely, narratives involving digital anomalies frequently feature fragmented plots and protagonists exhibiting emotional instability. Although these digital narratives may captivate and amuse children, they often lack explicit moral lessons. This study proposes a pedagogical approach integrating folktales' ethical clarity with digital media's format.